2021
DOI: 10.1108/lht-12-2020-0322
|View full text |Cite
|
Sign up to set email alerts
|

Impact of conspiracy beliefs on Covid-19 fear and health protective behavior: a case of university students

Abstract: PurposeThis study investigated the impact of conspiracy beliefs on fear of Covid-19 and health protective behavior of university students in Pakistan.Design/methodology/approachA cross-sectional survey using an online questionnaire was conducted at three universities in Punjab (e.g. two public sectors and one private sector) with permission from concerned authorities for data collection. A total of 374 responses were received that were analyzed by applying both descriptive and inferential statistics.FindingsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…The mean FCV-19S score of medical faculty students was determined as 16.7 ± 5.3 (Nguyen et al , 2020). In a study conducted with university students in Pakistan, the mean FCV-19S score was determined 3.5 ± 1.0 (Naveed et al , 2021). In this study, mean FCV-19S score of university students receiving health sciences education was 17.8 ± 5.3 points.…”
Section: Discussionmentioning
confidence: 99%
“…The mean FCV-19S score of medical faculty students was determined as 16.7 ± 5.3 (Nguyen et al , 2020). In a study conducted with university students in Pakistan, the mean FCV-19S score was determined 3.5 ± 1.0 (Naveed et al , 2021). In this study, mean FCV-19S score of university students receiving health sciences education was 17.8 ± 5.3 points.…”
Section: Discussionmentioning
confidence: 99%
“…Readers may also be interested in some articles on related information behaviour in Part I of our special issue (Huang et al , 2021). A cross-sectional survey (Naveed et al , 2021) showed the prevalence of conspiracy beliefs and fear of COVID-19 among Pakistan university students and how their conspiracy beliefs could predict their fear of COVID-19. Nguyen and Le (2021) investigated how to strengthen the uptake of older people's COVID-19 behavioural outcomes due to information value and perceived threat through social media, which presented plausible reasons for behavioural disclosure, including facemask wearing, handwashing and social distancing.…”
Section: Public Perception Of Covid-19 Vaccination and Social Distancingmentioning
confidence: 99%
“…One hot issue related to electronic news, especially on social media and other electronic means, is the spreading of misinformation and fake news (Naveed et al , 2021; Au et al , 2021a, b; Ho et al , 2022). In the issue, Zhang et al (2022) studied the features of health misinformation on social media sites (SMSs) to help easy identification by users and social media companies.…”
Section: Digital News and Readingmentioning
confidence: 99%